Piezoelectric Transducers and Applications - Arnau Vives, Antonio.; Arnau Vives, Antonio. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
New understandings underlying the principles of Piezoelectric Transducers, new technological advances in its applications, and new areas of utility for these transducers made a second edition of this book inevitable. The second edition of Piezoelectric Transducers and Applications includes these new developments together with a deep revision and enlargement of the topics already included in the first edition. It provides a guide for graduate students and researchers to the current state of the art of this complex and multidisciplinary area. The book fills an urgent need for a unified source of information on piezoelectric devices and their astounding variety of existing and emerging applications. Some of the chapters focus more on the basic concepts of the different disciplines involved and are presented in a didactic manner. Others go deeper into the complex aspects of specific fields of research, thus reaching the technical level of a scientific paper. Among other topics resonant sensors, especially bulk acoustic wave thickness shear mode resonators, chemical and bio-sensors, as well as broadband ultrasonic systems are treated in-depth.